AN ADAPTIVE VARIATIONAL MODEL FOR MEDICAL IMAGES RESTORATION - T. T. T. Tran; C. T. Pham; A. V. Kopylov; V. N. Nguyen (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
Image denoising is one of the important tasks required by medical imaging analysis. In this work, we investigate an adaptive variation model for medical images restoration. In the proposed model, we have used the first-order total variation combined with Laplacian regularizer to eliminate the staircase effect in the first-order TV model while preserve edges of object in the piecewise constant image. We also propose an instance of Split Bregman method to solve the proposed denoising model as an optimization problem. Experimental results from mixed Poisson-Gaussian noise are given to demonstrate that our proposed approach outperforms the related methods.